Copper(II) complexes of methylated glycine derivatives: Effect of methyl substituent on their DNA binding and nucleolytic property - Seng, H.L.; Ng, C.H.; Chikira, M.; Hamada, H.; Tan, W.T.; Maah, M.J.; Tan, K.W. (2009)
A set of copper(II) complexes of glycine and methylated glycine derivatives, Cu(aa)(2), consisting of C-dimethylglycine, L-alanine, N-dimethylglycine and sarcosine, was investigated for their DNA binding and nucleolytic properties by means of EPR and visible spectroscopy, and electrophoresis. They bind weakly to DNA with apparent binding constants in the range 1.8-2.9 x 10(3) M-1 with very similar orientation. No DNA cleavage is observed in the absence of exogenous agents. Copper(II) complexes of N-methylated derivatives bind to DNA more stereo-specifically and less strongly, and their oxidative DNA cleavage is less efficient than those of the corresponding C-methylated derivatives in the presence of hydrogen peroxide (H2O2) alone, or sodium ascorbate (NaHA) alone or tandem H2O2-NaHA. The oxidative DNA cleavage mechanism in the three systems involves a common copper(I) species. Neocuproine can inhibit DNA cleavage by these complexes. (C) 2009 Elsevier Ltd. All rights reserved.